P154 Tumor treating fields (200 kHz) concomitant with weekly paclitaxel for platinum-resistant ovarian cancer: phase 3 INNOVATE/ENGOT-ov50 study. (1st November 2019) - Vergote, I; Copeland, L; Monk, B; Coleman, R; Cibula, D; Sehouli, J; Samartzis, EP; Madry, R; González Martin, A; Korach, J; Salutari, V; Witteveen, PO; et al.
Abstract : Introduction/Background: Tumor Treating Fields (TTFields) are a non-invasive, regional antimitotic therapy. The Phase 2 INNOVATE study [NCT02244502 ] demonstrated safety of TTFields plus weekly paclitaxel in 31 PROC (platinum-resistant ovarian cancer) patients ( Vergote et al Gyn Onc 2018;150:471 ). No increase in grade 3–4 TTFields reported; 26 patients (84%) had TTFields-related dermatitis; one patient permanently discontinued TTFields due to dermatitis. Patients received median of 4 prior therapies; 100% prior platinum and 97% prior taxanes. Median PFS was 8.9 months, 25% had partial response and clinical benefit rate was 71%. The median overall survival was not reached: the one-year survival rate was 61%. This phase 3 INNOVATE-3/ENGOT-ov50 study investigates TTFields combined with weekly paclitaxel in PROC patients. Methodology: Patients (N=540) will have PROC (per RECIST V1.1) within 6 months of last platinum therapy with a maximum of 2–5 prior lines of systemic therapy, ECOG score of 0–1 and no peripheral neuropathy above grade1. Patients with primary refractory disease (progression during first line therapy) will be excluded. Patients will be randomized 1:1 to either weekly paclitaxel alone or weekly paclitaxel plus TTFields (200 kHz). Weekly paclitaxel will be administered at standard starting of dose 80 mg/m 2 weekly for 8 weeks, and then on Days 1, 8, and 15 for subsequent 28-day cycle. TTFields will be delivered for 18 hours/day and continued if no progression in the abdominal or pelvic regions ('in-field region') per RECIST V1.1. Clinical follow up will be performed q4w, with radiological follow up (CT or MRI scans of the abdomen and chest) q8w. The primary endpoint is overall survival. Main secondary endpoints: progression-free survival, objective response rate, severity and frequency of AEs, and quality of life (EORTC QLQ-C30 with QLQ-OV28). Sample size (n=540) will detect an increase in median overall survival from 12 to 16 months (Hazard ratio 0.75). Results: N/A TiP. Conclusion: N/A TiP. Disclosure: Ignace Vergote declares: Grants (Amgen and Roche);Consulting and advisory board (Roche, Genmab, Advaxis, Morphotek, Hoffmann-La Roche, Cerculean Pharma Inc., Novocure GmBh, Astrazeneca, Mateon Therapeutics Inc., Immunogen Inc., Eli Lilly Benelux NV, Amgen Inc., Theradex Europe Limited, Pfizer Inc., Debiopharma International SA, Vifor Pharma België, Novartis Pharma AG, MSD Belgium BVBA, Janssen-Cilag, Bayer Pharma AG, Clovis Oncology, Takeda, Pharma Mar, Oncoinvent, − Contracted Research by Morphotek and travel expenses sponsored by Tesaro, Clovis Oncology, Takeda, Pharma Mar, Roche, Genmab and Oncoinvent.